Uninsured Health Shocks and Agricultural Productivity among Rural Households: The Mitigating Role of Micro-credit. - Isoto, Rosemary E.; Sam, Abdoul G.; Kraybill, David S. (Journal of Development Studies, 2017)
This article investigates how health shocks affect farm productivity in the presence of microcredit. It is expected that microcredit increases agricultural productivity by enhancing allocative and technical efficiency and by overcoming financial constraints that reduce purchase of inputs. However, microcredit will have competing uses in the event of uninsured health shocks to the household. Using an endogenous switching regression model and after accounting for self-selection, the results reveal that microcredit has a significant mitigating effect on farm productivity losses. Thus, microcredit generates a double dividend among smallholders serving as insurance against health shocks in rural areas and improving agricultural productivity.